2019
DOI: 10.4314/tjpr.v18i2.29
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing community pharmacists’ recommendation of over-the-counter medications in four Vietnam cities

Abstract: Purpose: To determine the factors influencing the recommendation of over-the-counter (OTC) medicines to patients by community pharmacists in Vietnam. Methods: The study was conducted at community pharmacies in Vietnam, from June 10 to October 30, 2017. A final data set for analysis of 422 questionnaires was completed by community pharmacists from four different cities in Vietnam. Exploratory factor analysis was used to determine potential factors underlying a set of 20 questions related to the research topic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
3
0
4
Order By: Relevance
“…The key economic variables considered in this study include the impact of the local economic situation i.e., exchange rates on procurement prices and costs of medicines and type of medicines to dispense, decreased consumption due to reduced capacity to pay for goods purchased, access to credit finance, incomes levels of consumers and willingness-to-pay or capacity to pay for recommenced medications, the impact of these on consumer behavior and the effectiveness of service provided by the pharmacist [20][21][22]. In the United Kingdom, a study showed that economic factors such as profit, pressures of excess stock, and product promotion by pharmaceutical marketing companies have a significant influence on the community with actions in particular with pharmacist-owners [23][24].…”
Section: Economic Factorsmentioning
confidence: 99%
“…The key economic variables considered in this study include the impact of the local economic situation i.e., exchange rates on procurement prices and costs of medicines and type of medicines to dispense, decreased consumption due to reduced capacity to pay for goods purchased, access to credit finance, incomes levels of consumers and willingness-to-pay or capacity to pay for recommenced medications, the impact of these on consumer behavior and the effectiveness of service provided by the pharmacist [20][21][22]. In the United Kingdom, a study showed that economic factors such as profit, pressures of excess stock, and product promotion by pharmaceutical marketing companies have a significant influence on the community with actions in particular with pharmacist-owners [23][24].…”
Section: Economic Factorsmentioning
confidence: 99%
“…Walaupun pelatihan juga dibutuhkan oleh apoteker untuk dapat mengotimalkan peran mereka dalam menangani minor ailments 23 , namun demikian, pelatihan bukan satu-satunya faktor yang mempengaruhi ketepatan pemberian rekomendasi oleh apoteker. Faktor terkait produk, pelanggan, reputasi merek dagang, dan ekonomi ditemukan memiliki pengaruh dalam menentukan pemilihan dan ketepatan rekomendasi produk obat oleh apoteker komunitas 21,43 . Oleh karena itu, selain identifikasi terkait kebutuhan bentuk dan materi pelatihan terkait tatalaksana minor ailments, penelitian yang bertujuan untuk identifikasi faktor yang mempengaruhi apoteker di Indonesia, khususnya Surabaya, dalam merekomendasikan obat swamedikasi perlu dilakukan.…”
Section: Kasusunclassified
“…Penelitian ini tidak dapat mengetahui secara pasti pertimbangan partisipan dalam memberikan rekomendasi. Merujuk pada penelitian terpublikasi yang dilakukan pada apoteker komunitas dapat diketahui bahwa terdapat faktor kompleks yang dapat mempengaruhi keputusan pemberian suatu rekomendasi, termasuk salah satunya faktor finansial [33,34]. Penelitian lebih lanjut dengan desain kualitatif perlu dilakukan untuk mengidentifikasi pertimbangan mahasiswa apoteker dalam memberikan rekomendasi.…”
Section: Hasil Dan Diskusiunclassified